ANN Based DC Link Control of STATCOM in Wind Integrated Distribution System for Power Quality Conditioning - Rani, S. K.; Prabakaran, S. (Engineering, Technology & Applied Science Research, 2020)
The integration of Renewable Energy Sources (RES) brings along abnormalities that affect the grid, loads, and may degrade the performance of the system. These issues can be alleviated with the integration of RES with the use of a distribution Static Synchronous Compensator (STATCOM). Renewable generation with STATCOM provides quality of power during disturbances created by the AC loads and intermittent power from the RES. The STATCOM distribution of DC link plays a major role in the supply quality during abnormalities. In this work, an attempt has been made to provide supply quality in the distribution system with the integration of a renewable energy farm using Artificial Neural Network (ANN)-based DC link STATCOM control of distribution. The wind farm is analyzed for a Double Fed Induction Generator (DFIG) based wind turbine system and it is integrated into the distribution system. The system was simulated in MATLAB 2018A.